2022
DOI: 10.1186/s43593-021-00009-5
|View full text |Cite
|
Sign up to set email alerts
|

Surface Dyakonov–Cherenkov radiation

Abstract: Recent advances in engineered material technologies (e.g., photonic crystals, metamaterials, plasmonics, etc.) provide valuable tools to control Cherenkov radiation. In all these approaches, however, the particle velocity is a key parameter to affect Cherenkov radiation in the designed material, while the influence of the particle trajectory is generally negligible. Here, we report on surface Dyakonov–Cherenkov radiation, i.e. the emission of directional Dyakonov surface waves from a swift charged particle mov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…As with other effects in the grazing-angle interaction zone, one can predict which SPP modes are excited by an electron with velocity reduced β by identifying the intersection of the dispersion relation with the electron line 159 ω(k ) = vk . Analogues of this effect have been observed in systems supporting Dyakonov surface waves 163 and hyperbolic dispersion. 110…”
Section: Coherent Excitation Of Surface Plasmon Polaritons (Spps) By ...supporting
confidence: 60%
“…As with other effects in the grazing-angle interaction zone, one can predict which SPP modes are excited by an electron with velocity reduced β by identifying the intersection of the dispersion relation with the electron line 159 ω(k ) = vk . Analogues of this effect have been observed in systems supporting Dyakonov surface waves 163 and hyperbolic dispersion. 110…”
Section: Coherent Excitation Of Surface Plasmon Polaritons (Spps) By ...supporting
confidence: 60%
“…Now a team led by Prof. Yu Luo from Singapore considers a situation when the particle emits surface electromagnetic waves at the interface between an isotropic and a uniaxial-birefringent medium (Dyakonov surface waves 6 ). The resulting Dyakonov-Cherenkov radiation is shown to be highly sensitive to both the value and the direction of the particle velocity 7 . In particular, it is shown that close to the Cherenkov threshold, the radiation intensity can be several orders of magnitude greater than that in traditional Cherenkov detectors.…”
mentioning
confidence: 99%
“…In the structural schematic shown in Figure 1a, the current density of a free electron J(truer¯,t)=trueẑveeδ(x)δ(yy0)δ(zvet)$J\ ( {\bar{r},t} ) = \hat{z}\ {v}_{\rm{e}}e\delta ( x )\delta ( {y - {y}_0} )\delta ( {z - {v}_{\rm{e}}t} )$ in the free space (with ε r1 = 1) induces a vector potential as [ 60,9 ] ϕ¯0badbreak=trueẑ+normaldkxnormalie8π2ky1enormalikxx+normaliky||yy0+normaliωvnormalez\begin{equation}{\bar{\phi }}_0 = \hat{z}\ \mathop \smallint \limits_{ - \infty }^{ + \infty } {\rm{d}}{k}_x\frac{{{\rm{i}}e}}{{8{\pi }^2{k}_{y1}}}{e}^{{\rm{i}}{k}_xx + {\rm{i}}{k}_y\left| {y - {y}_0} \right| + {\rm{i}}\frac{\omega }{{{v}_{\rm{e}}}}z}\end{equation}where e is the elementary charge. The vector potential enables to determine the source field of the free electron as lefttrueE¯()r¯,ωgoodbreak=iωε0××ϕ¯0lefttrueH¯()r¯,ωgoodbreak=×ϕ¯0\begin{equation} \left\{ \def\eqcellsep{&}\begin{array}{l}\bar{E}\left(\bar{r},\omega \right)=\frac{\mathrm{i}}{\omega {\varepsilon}_{0}}\nabla \ensuremath{\times{}}\nabla \ensuremath{\times{}}{\bar{\phi}}_{0}\\ \bar{H}\left(\bar{r},\omega \right)=\nabla \ensuremath{\times{}}{\bar{\phi}}_{0}\end{array} \right.…”
Section: Methodsmentioning
confidence: 99%